The Relationship between Self-Assessed Intelligence and Self-Assessed Personality, Tolerance of Uncertainty and the Dark Triad Traits in Managers - Юлия Владимировна Красавцева (Psychology. Journal of the Higher School of Economics, 2018)
In this study we present the empirical results on the evaluation of relationships between three personality traits — subclinical narcissism, subclinical psychopathy and Machiavellianism, — collaboratively known as the Dark Triad, with tolerance of uncertainty and direct self-assessments of intelligence and personality. A group of Russian adults in managerial positions were tested: we measured levels of personality features via questionnaires and asked participants to estimate their IQ scores using a normal distribution graph, and, in a similar manner, to evaluate the location for their personality on a polar graph of “bad” and “good” in two conditions: (1) at the moment and (2) if circumstances were different. We found that the higher managers rated their intelligence, the “better” they estimated their personalities to be. Also, tolerant to uncertainty managers considered their IQ to be higher and their personalities, both at the moment and if circumstances were to change, to be “better”. Finally, managers with higher levels of narcissism and Machiavellianism rated their intelligence and personality higher, while those with lower levels of subclinical psychopathy tended to assume that their personality could be “better” under different circumstances. Cognitive and personality components of self-regulation and self-awareness may be regarded as a complex and multi-dimensional area for further research, as, among other factors, self-assessment serves as a direct and indirect association between the widely regarded positive personality features (tolerance of uncertainty) and the Dark Triad traits.